Dagdag-bawas a total weight management resort for people with obesity and eating disorders - Gacula, Mary Pauleen M.; Sarthou, Armin Jr. B. (2009)
Medical Tourism has been an emerging trend and is dominated by Asian countries over the past years. With this, it was given that the government has included in its Medium Term Development Plan of 2004-2010 the aim to develop the medical tourism industry in the Philippines. Together with the aim to promote health and wellness throughout the country, the emergence of new combinations of recreation and healthcare has been popular. This thesis, entitled Daadag-Bawas : a Total Weight Management Resort for People with Obesity and Eating Disorders, is an approach to creating the combination of receration and wellness for the sake of promoting medical tourism as well as healthy living to Filipinos and to the foreign market. The problem started from the issue of body image ideals set by media which had brought negative effects to the people. Most people desire to achieve the accepted stereotypes and tend to be addicted to weight loss. The approach to this is the creation of a facility/complex which can completely direct people to use proper weight loss methods and to learn to adapt to a healthier lifestyle. The research phase dwells into understanding the cause of eating disorders and unhealthy lifestyles and then formulating a list of facilities needed to create a total weight management complex. The outcomes are based on data gathering, interviews and existing similar facilities. The proposed resulting facility aims to provide an effective solution to targeting total weight management. It also aims to expand existing fitness centers in the country by relating medical systems to the overall service needed and demanded by the local and foreign market.
Vita.
Thesis (Bachelor of Science in Architecture)--University of the Philippines Diliman.
Keywords: Health and Wellness Facility -- Design